TOURISM IN THE ECONOMY OF THE ROLE OF STATISTICAL EVALUATION METHODOLOGY - Zilola Jumanova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Article tourism in the economy of the fastest eguluvchan activities, the sensitivity is high , and tourism is an important factor in the development of the economy that is based on fact. Discusses statistical methods to determine the role of tourism in the national and regional economy. To identify indicators of the development of tourism representingthe nga. In assessing the role in the tourism economy directly depends upon the macroeconomic sphere korrelyativ with each analysis that was made. Changing many rows-time data for the analysis of ARDS (Autoregressive distributed lag) model ekonometrik using equation was based on